Delimiting the social boundaries of competition law in asean: a common approach? - Ahamat, Haniff; Abdul Rahman, Nasarudin (International Islamic University Malaysia, 2014)
This paper examines the interface between the economic and social elements of competition law in ASEAN. Generally, the aim of competition law should be to protect the process of competition, promote market efficiencies and enhance consumer welfare in the countries. Nevertheless there is a concern arising from such interface. Competition law strives to ensure competition and economic efficiency but market structure and behavior which harm competition or lead to inefficiency may have positive impact on the society. Along these lines, this paper looks into the social applications of competition legislation of Thailand, Indonesia, Singapore and Malaysia. Variations between different ASE